Pengaruh Shopping Lifestyle, Hedonic Shopping Motivation, dan Discount terhadap Impulse Buying Produk Skincare Skintific di TikTok Shop (Studi pada Mahasiswi Kota Malang) - Reska, Moudita Nafianti; Basalamah, Muhammad Ridwan; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze the influence of shopping lifestyle, hedonic shopping motivation, and discounts on impulse buying of Skintific skincare products at the TikTok Shop. The research method used is a quantitative research method. Sampling was carried out on female students in Malang City, using the Maholtra formula so that the sample obtained in this study was 80 respondents who were taken using a purposive sampling technique with criteria determined by the researcher. To obtain data, this research used a data collection method with a questionnaire. The data analysis used is instrument testing, normality testing, classical assumptions, multiple linear regression analysis, hypothesis testing, and coefficient of determination using the SPSS 25 application. The results of this study show that shopping lifestyle, hedonic shopping motivation, and discounts have a positive and significant effect simultaneously. on impulse buying Skintific skincare products on the TikTok Shop. Furthermore, partially, shopping lifestyle, hedonic shopping motivation, and discounts have a positive and significant effect on impulse buying of Skintific skincare products on the TikTok Shop. Keywords: Shopping lifestyle, Hedonic Shopping Motivation, Discount, Impulse Buying.